2019
DOI: 10.3390/ijms20143467
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Scorpion Neurotoxin AaIT against Insect Pests

Abstract: Androctonus australis Hector insect toxin (AaIT), an insect-selective toxin, was identified in the venom of the scorpion Androctonus australis. The exclusive and specific target of the toxin is the voltage-gated sodium channels of the insect, resulting in fast excitatory paralysis and even death. Because of its strict toxic selectivity and high bioactivity, AaIT has been widely used in experiments exploring pest bio-control. Recombinant expression of AaIT in a baculovirus or a fungus can increase their virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…given the previously successful transgenic use of this toxin against early larval stages of DBM and other lepidopterans (21). In addition to being of fundamental interest, the above results are consistent with previous findings in Ae.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…given the previously successful transgenic use of this toxin against early larval stages of DBM and other lepidopterans (21). In addition to being of fundamental interest, the above results are consistent with previous findings in Ae.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies involving the engineering of AaHIT into baculoviruses and Bt have demonstrated a significantly increased lethality to larval stages of DBM (21).…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies involving the engineering of AaHIT into baculoviruses and Bt have demonstrated a significantly increased lethality to larval stages of DBM. 24 As such, we first set out to assess whether the transgenic expression of the synthetic AaHIT neurotoxin affected survival to pupation and/or adult eclosion. Hr5/ie1-tTAV and Op/ie2-tTAV heterozygotes were crossed to tetO-AaHIT line heterozygotes en masse (for example, Hr5/ie1-tTAV males × tetO-AaHIT females and vice versa).…”
Section: Resultsmentioning
confidence: 99%
“…This allowed use of the female fat-body-specific promoter from the VitellogeninA1 gene even though expression of cell-autonomous effectors (Michelob, Reaper KR ) using this promoter had no observable effect. 23 The AaHIT gene has also been used to increase the potency of a variety of biocontrol technologies targeting lepidopteran pests including engineering its expression in recombinant Bt and Autographa californica baculovirus, both tested against DBM, 24 and thus we hypothesized that such an AaHIT-based non-cellautonomous system could also function in this species. Here, we extend our previous work in mosquitos to DBM using the same bipartite 'tet-off' gene expression system utilized in the DBM female-lethal GPM system.…”
Section: Introductionmentioning
confidence: 99%
“…An insect-selective neurotoxic polypeptide derived from scorpion venom (AaIT), has recently been used to engineer different organisms such as viruses, fungi, bacteria and plants against insect pests (Deng et al, 2019). Many types of different baculoviruses including AaIT gene have been constructed to enhance the insecticidal activity against lepidopteran larvae (Treacy & All, 1996;Yao et al, 1996;Elazar et al, 2001).…”
Section: Discussionmentioning
confidence: 99%